Pulmonary Agenesis and Associated Pulmonary Hypertension: A Case Report and Review on Variability, Therapy, and Outcome - Oliver Muensterer; Rosanna Abellar; David Otterburn; Rajamma Mathew (Georg Thieme Verlag KG, 2015)
Abstract Pulmonary agenesis is a rare congenital disorder with large variability in presentation and prognosis. We describe a full-term infant born with right-sided pulmonary agenesis who underwent thoracoscopic placement of a tissue expander. He ultimately died of pulmonary hypertension. Immunohistology showed intimal hyperplasia without the loss of endothelial caveolin-1 expression. A literature review revealed that while some of these patients have favorable outcome, many succumb despite therapy.